PENGARUH KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KANTOR CABANG PT. ASURANSI JASINDO PALEMBANG - Nur Effen (Fakultas Ekonomi Universitas Tridinanti Palembang, 2016)
This study examined the phenomenon of employee performance at PT. Asuransi Jasindo in Palembang. The purpose of research aims to know the influence of Leadership and motivation and working discipline to the employees performance. The research method used were descriptive and verificative , and analysis method used multiple regression, multiple correlation and determination method. This study shows that the Leadership, Motivation and Working Discipline has significant influence toward employee performance, but partially leadership also identifies dominant variables to influence the employee performance. Key words : Performance, Leadership, Motivation and Working Discipline.